Efficacy and Safety of Endoscopic Papillary Large Balloon Dilation for Removal of Large Bile Duct Stones in Advanced Age - Kook Hyun Kim; Tae Nyeun Kim (Canadian Journal of Gastroenterology and Hepatology)
Objective. Bile duct stone-related adverse events can be detrimental in the elderly. However, little is known about clinical outcomes and adverse events following endoscopic papillary large balloon dilation (EPLBD) in the elderly. The aim of this study was to evaluate the safety and feasibility of EPLBD for the removal of CBD stones in patients aged ≥ 80 years. Methods. A total of 204 patients who underwent EPLBD from 2006 to 2012 were retrospectively reviewed. Patients were classified into two groups (148 patients < 80 years old, Group A; 56 patients ≥ 80 years old, Group B). Endoscopic findings, clinical outcomes, and adverse events in two groups were compared. Results. The number of underlying chronic diseases in Group B was significantly higher than in Group A (P=0.032). The rates of overall stone clearance were similar between two groups (P=0.145). No significant difference with regard to post-ERCP pancreatitis between two groups was observed (P=0.687). All episodes of pancreatitis had full recovery with conservative treatment. One major hemorrhage in Group A was successfully controlled endoscopically and one death caused by retroperitoneal perforation occurred in Group A. Conclusions. EPLBD appear to be safe and effective for CBD stone removal in patients aged ≥ 80 years.